1999
DOI: 10.1007/pl00006795
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Effect of Outer-Membrane Proteins from Campylobacter jejuni on Chicken Lymphocytes

Abstract: Campylobacter jejuni is a significant cause of food-borne diseases in humans. The bacterium is considered a commensal organism in chickens, and it can heavily colonize chickens without causing inflammation. Poultry may be the major reservoir for the human infection in developed countries. Here we show that an outer-membrane protein extract prepared from the bacteria caused apoptosis of chicken lymphocytes detected in vitro with the terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling assay tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
0
15
1
Order By: Relevance
“…The enteric bacteria cause more than 50% of cell death within a few hours. In contrast, H. pylori induced only up to 25% of host cell death in 24 h. In Pseudomonas aeruginosa (12) and Campylobacter jejuni (77), apoptotic activities of the outer membrane porins have been identified. Incubation of the porins purified from these organisms with the host cell causes a rather small degree of apoptosis (12,77), which is comparable to that of H. pylori.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enteric bacteria cause more than 50% of cell death within a few hours. In contrast, H. pylori induced only up to 25% of host cell death in 24 h. In Pseudomonas aeruginosa (12) and Campylobacter jejuni (77), apoptotic activities of the outer membrane porins have been identified. Incubation of the porins purified from these organisms with the host cell causes a rather small degree of apoptosis (12,77), which is comparable to that of H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, H. pylori induced only up to 25% of host cell death in 24 h. In Pseudomonas aeruginosa (12) and Campylobacter jejuni (77), apoptotic activities of the outer membrane porins have been identified. Incubation of the porins purified from these organisms with the host cell causes a rather small degree of apoptosis (12,77), which is comparable to that of H. pylori. In this mechanism, by interacting with the plasma membranes of the host cells, porins become embedded as hydrophilic pores in the phospholipid bilayer, damaging the structure and function of this part of the host cell architecture and leading to the activation of apoptotic signaling pathways (12).…”
Section: Discussionmentioning
confidence: 99%
“…Both previous reports of induction of apoptosis by C. jejuni in either chicken lymphocytes (24) or human monocytes (20) indicated that PCD was independent of CjCDT, although limited data were presented. Siegesmund et al (20) reported that apoptosis of THP-1 monocytes required, instead, secretion of the Cia (campylobacter invasion antigen) proteins that are secreted through the flagellar secretion apparatus (10,11,18).…”
mentioning
confidence: 93%
“…CDTs from other bacteria are also known to target immune cells and ultimately induce apoptosis (3,19,21). There have been two reports of apoptotic responses to C. jejuni (20,24), and both suggested that mechanisms independent of CDT were responsible. Here, we confirm earlier observations of long-term campylobacter survival and replication within monocytes and the induction of apoptosis.…”
mentioning
confidence: 99%
“…A cytotoxicnecrotizing-factor-producing strain of E. coli also with CDT activity, BM2-1, induces apoptotic cell death (De Rycke et al, 1996). It is also noteworthy that C. jejuni outer-membrane proteins cause apoptosis of chicken lymphocytes (Zhu et al, 1999). Furthermore, H. ducreyi CDT is responsible for apoptosis in Jurkat cells (Gelfanova et al, 1999), and A. actinomycetemcomitans causes murine macrophage apoptosis (Kato et al, 1995).…”
Section: Discussionmentioning
confidence: 99%